2017
DOI: 10.1074/jbc.m117.797126
|View full text |Cite
|
Sign up to set email alerts
|

The intracellular chloride channel proteins CLIC1 and CLIC4 induce IL-1β transcription and activate the NLRP3 inflammasome

Abstract: The NLRP3 inflammasome is a multiprotein complex that regulates the activation of caspase-1 leading to the maturation of the proinflammatory cytokines IL-1β and IL-18, and promoting pyroptosis. Classically, the NLRP3 inflammasome in murine macrophages is activated by the recognition of pathogen-associated molecular patterns and by many structurally unrelated factors. Understanding the precise mechanism of NLRP3 activation by such wide array of stimuli remains elusive, but several signaling events, including cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 53 publications
3
116
0
1
Order By: Relevance
“…Concurrently, NEK7 was also identified by He et al to drive NLRP3 activation, and further attributed NEK7 activation to potassium (K + ) efflux, suggesting NEK7 acts as both an ion and ROS sensor. The efflux of cytosolic K + is a known trigger for NLRP3 inflammasome activation, and furthermore the chloride intracellular channel (CLIC) proteins CLIC1 and CLIC4 have been shown to impact on Il1β transcription and NLRP3 inflammasome activation . CLICs have been shown to be activated downstream of K + efflux and ROS.…”
Section: Redox Sensing In Nlrp3 Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, NEK7 was also identified by He et al to drive NLRP3 activation, and further attributed NEK7 activation to potassium (K + ) efflux, suggesting NEK7 acts as both an ion and ROS sensor. The efflux of cytosolic K + is a known trigger for NLRP3 inflammasome activation, and furthermore the chloride intracellular channel (CLIC) proteins CLIC1 and CLIC4 have been shown to impact on Il1β transcription and NLRP3 inflammasome activation . CLICs have been shown to be activated downstream of K + efflux and ROS.…”
Section: Redox Sensing In Nlrp3 Activationmentioning
confidence: 99%
“…The efflux of cytosolic K + is a known trigger for NLRP3 inflammasome activation, 23 and furthermore the chloride intracellular channel (CLIC) proteins CLIC1 and CLIC4 have been shown to impact on Il1β transcription and NLRP3 inflammasome activation. 24 CLICs have been shown to be activated downstream of K + efflux and ROS. Mitochondrial ROS has been shown to drive translocation of CLICs to the plasma membrane where they cause chloride efflux.…”
Section: Redox Sensing In Nlrp3 Activationmentioning
confidence: 99%
“…Upon overexpression, CLIC3 and CLIC4 are localized to the nucleus of Cercopithecus aethiops monkey kidneys (CV)-1 (Qian, Okuhara, Abe, & Rosner, 1999) and HeLa cells (Argenzio et al, 2014) This is surprising given CLIC3 lacks the canonical NLS, possibly possessing a non-canonical NLS that is yet to be characterized. In bone marrow-derived macrophages, CLIC4 is observed in the nucleus and its expression increases with lipopolysaccharide (LPS) stimulation (Domingo-Fernandez, Coll, Kearney, Breit, & O'Neill, 2017). Hepatocellular cancer (HCC) cell lines (HepG2, Huh7, and SNU387) have native CLIC5 in the nucleus (Flores-Tellez, Lopez, Vasquez Garzon, & Villa-Trevino, 2015) and ectopic expression in HeLa cells localizes CLIC5 to the nucleus (Al-Momany, Li, Alexander, & Ballermann, 2014).…”
Section: Nucleusmentioning
confidence: 99%
“…The most important results of the present study are those clarifying the involvement of the PI3K/AKT/mTOR and JAK/STAT3 signaling pathways in the Cl − channel/transporter‐induced modification of HER2 transcription in breast cancer cells. A previous study reported that CLIC1 promoted transcription of the pro‐inflammatory cytokine, interleukin (IL)‐1β in LPS‐stimulated macrophages . Among the 6 members of intracellular Cl − channels, CLIC, CLIC1 was predominantly expressed in MDA‐MB‐453 and YMB‐1 cells (Figures D and B); however, the siRNA‐mediated inhibition of CLIC1 did not repress HER2 transcription in either cell (Figures A and C).…”
Section: Discussionmentioning
confidence: 90%